The effect of mobile learning application in enhancing students’ knowledge of caring sepsis patients - Efris Kartika Sari; Dewi Purnama Sari (International Journal of Public Health Science (IJPHS), 2023)
Sepsis is one of the major causes of death in hospitalized worldwide, but there are many nurses who have insufficient knowledge about sepsis. The use of mobile phones as learning devices potentially improves knowledge in nursing education in the pre-clinical stage. The study aimed to determine the effectiveness of mobile learning application in improving nursing students’ knowledge about sepsis and its nursing care. This research was a pre-experimental study with the one-group pretest-posttest design. The study involved 57 students in the Nursing Department, Faculty of Medicine, Brawijaya University. Their knowledge levels were measured before and after they used mobile learning applications. The nursing students’ age was 19-24 years old; 93% were female; 82% of students had received information about sepsis from course materials and the internet, and 65% were currently studying the Nursing Profession Program. The median value of the interquartile range pretest was 40+20, and 70+30 for the posttest. The statistical test showed a significance value of 0.000 (p<0.05); there were significant differences in students’ knowledge levels before and after using the mobile learning application. Using the mobile learning application can effectively enhance nursing students’ understanding of sepsis care.